2014
DOI: 10.3109/13561820.2014.907779
|View full text |Cite
|
Sign up to set email alerts
|

The student-run free clinic: an ideal site to teach interprofessional education?

Abstract: Student-run free clinics (SRFCs) often include an interprofessional group of health professions students and preceptors working together toward the common goal of caring for underserved populations. Therefore, it would seem that these clinics would be an ideal place for students to participate in an interprofessional collaborative practice and for interprofessional education to occur. This article describes a prospective, observational cohort study of interprofessional attitudes and skills including communicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
65
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(66 citation statements)
references
References 16 publications
1
65
0
Order By: Relevance
“…Our results are similar to those of previous studies, which found that volunteering at an SRC improves student attitudes toward other HCPs and IPC 7,10,15,16 and their understanding of other HCP roles. 6,16,26 Learning about collaboration and the roles of other HCPs are important elements of IPE.…”
Section: Inter-professional Interactionssupporting
confidence: 91%
See 1 more Smart Citation
“…Our results are similar to those of previous studies, which found that volunteering at an SRC improves student attitudes toward other HCPs and IPC 7,10,15,16 and their understanding of other HCP roles. 6,16,26 Learning about collaboration and the roles of other HCPs are important elements of IPE.…”
Section: Inter-professional Interactionssupporting
confidence: 91%
“…1 SRCs are an increasingly common setting for an authentic IPE experience. [5][6][7][8] At SRCs, students oversee clinical operations and provide primary health care services to patients under the guidance of preceptors. 6,8,9 Many SRCs include an interdisciplinary group of students who work together to serve marginalized patient populations presenting with complex health care needs.…”
Section: Ré Sumémentioning
confidence: 99%
“…Attention must be paid to frequent participation, training, and physical space for sharing patient information, cross-disciplinary networking, and reflection. 8 We hope to explore such aspects in the future.…”
Section: Interprofessional Collaborationmentioning
confidence: 99%
“…2,7 Healthcare profession students who plan to work as providers in interprofessional collaborative practices must learn in interprofessional settings. 8 Community-based clinics can be excellent examples of such settings where students collaborate with other health care professionals to provide chronic disease management. 9 Students also develop an understanding of the value and contribution of other professionals when they cooperate with and share resources across professions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation